Exploring the offshore wind energy potential of Turkey based on multi-criteria site selection. (January 2019) - Argin, Mehmet; Yerci, Volkan; Erdogan, Nuh; Kucuksari, Sadik; Cali, Umit
Abstract: Wind energy is the leading form of non-hydro renewable energy source in terms of installed capacity in Turkey. It is among the most promising option for Turkey to decrease the energy dependence of external primary energy resources such as national gas and oil that diversifies the domestic share of energy sources in the national energy mix. However, offshore wind energy deployment has not gained satisfactory attention even though the country is surrounded by seas on three of its sides. Exploring Turkey's offshore wind power potential becomes an important task to serve this energy policy. This study presents a methodological framework for finding the most suitable offshore wind farm locations, meeting various multi-layer site selection criteria. The offshore wind energy resource is first assessed using the wind energy potential for 55 coastal regions where the nearshore meteorological stations are available in Turkey. Following on this analysis, a multi-criteria site selection work is carried out to identify the most suitable areas for offshore wind development. Wind Atlas Analysis and Application Program (WAsP) is then used to conduct statistical analysis to identify the most promising offshore wind farm locations. According to the pre-processing step of the framework, Bozcaada, Bandirma, Gokceada, Inebolu, and Samandag coastlines are found to be the most suitable locations for offshore wind farm development. Finally, the offshore wind energy potential of Turkey is estimated by using the micro-sitting configuration of wind turbines, considering sea depth, main wind direction, and distance to shore for the most feasible project locations. It is found that total estimated offshore wind power capacity at the specified sites is 1, 629 MW. Highlights: The offshore wind energy potential of Turkey is identified. Bozcaada, Bandirma, Gokceada, Inebolu, and Samandag are the most suitable locations for offshore wind energy development. The offshore wind power potential of Turkey at the specified sites is estimated to be 1629 MW.